2018
DOI: 10.3390/ijerph15081672
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Associated with Exposure to PM10 and Benzene in Three Italian Towns

Abstract: Air pollution in urban areas is a major concern as it negatively affects the health of a large number of people. The purpose of this study was to assess the inhalation health risk for exposure to PM10 and benzene of the populations living in three Italian cities. Data regarding PM10 and benzene daily measured by “traffic” stations and “background” stations in Torino, Perugia, and Lecce during 2014 and 2015 were compared to the limits indicated in the Directive 2008/50/EC. In addition, an inhalation risk analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 34 publications
(42 reference statements)
0
13
0
1
Order By: Relevance
“…Male mice exposed to benzene developed hyperglycemia and hyperinsulinemia followed by elevated expression of hepatic gluconeogenic and lipid metabolism genes. The association between benzene exposure and insulin resistance was reported in a few epidemiological and rodent studies [23,26,27,43,55,56]. Studies in humans found that the elimination of benzene is slower in women than in men, likely due to the higher percentage and distribution of body fat tissue [57].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Male mice exposed to benzene developed hyperglycemia and hyperinsulinemia followed by elevated expression of hepatic gluconeogenic and lipid metabolism genes. The association between benzene exposure and insulin resistance was reported in a few epidemiological and rodent studies [23,26,27,43,55,56]. Studies in humans found that the elimination of benzene is slower in women than in men, likely due to the higher percentage and distribution of body fat tissue [57].…”
Section: Discussionmentioning
confidence: 94%
“…Supplementary Figure 1A depicts a schematic of the exposure protocol in benzene inhalation chambers. This adapted regimen for benzene inhalation resembles human benzene exposure levels in highly polluted gas stations, or exposure to tobacco smoke or e-cigarette vapors aerosols [12,43,44]. Under these conditions, benzene exposure had no effect in white blood cell counts in benzene exposed animals versus control animals breathing room air (Supplementary Figure 1D), while levels of the urine benzene metabolite, t,t-MA were significantly increased in benzene exposed mice (Supplementary Figure 1E).…”
Section: Benzene Exposure Induces Hyperglycemia and Hyperinsulinemia mentioning
confidence: 94%
“…Exposure to high PM levels is a potential health risk for humans, as inhaled particulates may reach different depths of the lungs, according to their size, causing severe adverse health effects. Several studies revealed the association of high PM levels with the increase of respiratory and cardiovascular pathology incidences [12][13][14][15][16]. Generally, natural sources emit particles with diameters above 2.5 µm, while anthropogenic sources emit fine and ultrafine particles.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1A illustrates a schematic timeline of the experimental design. This adapted regimen for benzene inhalation resembles chronic human benzene exposure levels in highly polluted gas stations, or exposure to tobacco smoke (De Donno et al 2018;Lorkiewicz et al 2019;Pankow et al 2017). We have recently demonstrated that under these conditions, benzene exposure has no significant changes in white blood cell counts in benzene exposed animals versus control animals breathing room air (Debarba et al 2020).…”
Section: Gestational Benzene Exposure Does Not Alter Body Weight In Tmentioning
confidence: 97%
“…Similarly, epidemiological data have shown a positive association between cigarette smoke exposure in utero and increased risk of obesity and metabolic imbalance in offspring (Behl et al 2013). A study of traffic pollutants (PM10 and benzene) in a community in northern Italy showed an association between exposure to PM10 and different birth defects (De Donno et al 2018).…”
Section: Introductionmentioning
confidence: 95%